Monte Carlo GEANT4 Simulation Approach in Analyzing Radiation Shielding Parameter of Lombok Pumice - Wirawan, Rahadi; Qomariyah, Nurul; Ardianto, Teguh; Kurniawidi, Dian Wijaya; Waris, Abdul; Djamal, Mitra (Trends in Sciences, 2022)
The linear attenuation coefficient (LAC), mean free path (MFP), half-value layer (HVL), and the radiation protection efficiency (RPE) parameters of Lombok pumice powder from 3 different regions (Ijobalit, Setangi beach, and Lingsar) have been analyzed. The radiation parameter analysis was carried out to determine the pumice that potential as a raw material of radiation shielding composite. The Monte Carlo simulation using the GEANT4 toolkit was applied to analyze those parameters using a gamma-ray transmission measurement for the photon energies of 57Co, 133Ba, 54Mn, 137Cs, 60Co, 65Zn, 22Na and 40K. The GEANT4 simulation results were compared to the XCOM theoretical calculation and show that the linear attenuation coefficient parameter has a good agreement with the XCOM results based on the determination coefficient of the correlation graph (R2 = 0.998) between those 2 approaches methods. Setangi beach pumice has a smaller LAC parameter than Ijobalit pumice and Lingsar pumice. The MFP and HVL parameter of the Setangi beach pumice indicate the absorption ability of gamma photons is low. In the low gamma energy 0.122 MeV, Ijobalit pumice and Lingsar pumice have more than 50 % RPE and are better used as a raw material of radiation shielding composite. HIGHLIGHTS New lead-free shielding materials of radiation becomes a critical concern in the investigation of raw shielding material GEANT4 Monte Carlo simulation and XCOM theoretical calculation was conducted to analyse the radiation LAC parameter Radiation parameters analysis of Lombok Pumice show that Ijobalit pumice and Lingsar pumice have more than 50 % RPE and are better used as a raw material of radiation shielding composite GRAPHICAL ABSTRACT